L’eau des riches - Fabienne Wateau (Ateliers d'Anthropologie)
Should marketing and advertising be seen as possible forms of cosmopolitanism? This article offers an analysis of methods of selling and distributing Perrier bottled water, sold internationally in the name of a national particularity—a characteristically French style and snobbery that gives it its mark of distinction. Cosmopolitanism is examined in light of this globalised market, while the principles of distinction are recalled to explain its success.